Effectiveness of digital platform in reducing unintentional medication discrepancies at transition of care from hospital discharge to primary healthcare settings: a randomised controlled trial - Phang, Yen Yen; Kuan, Jew Win; Oh, Ai Ling; Ting, Chuo Yew; Nor Anizah, Osman; Stephen, Moses (BioMed Central Ltd., 2025)
Background Modifications to medication regimens during transitions of care between different healthcare settings often lead to unintentional medication discrepancies (UMDs). The MedBook Portal, a simple digital platform that enables the sharing of patient medication records among healthcare facilities under Ministry of Health, was developed to facilitate medication reconciliation at primary health clinic (PHC) after hospital discharge. This study aimed to determine the effectiveness of MedBook Portal in reducing UMDs in the first prescription during the first PHC visit after hospital discharge. Methods This two-arm, parallel, non-blinded, randomised controlled trial was conducted at four public hospitals and ten public PHCs in Sarawak, Malaysia, from May 2023 to July 2024. Adult patients aged ≥ 18 years in general medical wards, discharged from hospitals, and referred to selected PHCs were recruited. In the Standard Care group, PHC doctors performed standard medication reconciliation by reviewing patients’ medical records on their home-based medical cards and discharge notes, if available. In the MedBook Portal group, in addition to this process, PHC doctors logged into MedBook Portal to access the discharge prescription before issuing a new prescription. Results Among the 339 eligible subjects randomised into MedBook Portal group and Standard Care group, 307 participants (147 MedBook Portal, 160 Standard Care) were analysed after excluding those for whom the intervention was not performed (n = 11) and those with no prescription (n = 21). The incidence rate of prescription with UMDs was significantly lower in the MedBook Portal group (5/147, 3.4%) compared to the Standard Care group (30/160, 18.8%) (p < 0.001). The most common UMD was drug omission (54.4%). Multivariable logistic regression showed that the presence of MedBook Portal reduced the odds of UMDs by 87% (adjusted OR 0.134, 95% CI 0.049–0.336, p < 0.001), whereas each additional comorbidity increased the odds by 52% (adjusted OR 1.520, 95% CI 1.158–2.020, p = 0.003).